Digital Advertising and Generation Z Online Spending in Indonesia’s Emerging Market: The Moderating Role of Advertising Relevance - Agung Wijoyo; Luh Nadi; Rodhiah (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose - The rapid expansion of Indonesia’s digital economy has intensified the strategic role of digital advertising in influencing consumer purchasing behavior, particularly among Generation Z consumers who actively engage with social media and e-commerce platforms. Although personalized and relevance-based advertising systems have become increasingly common, empirical evidence regarding how digital advertising effectiveness influences actual online spending behavior remains limited and inconsistent. This study therefore examines the effect of digital advertising effectiveness on Generation Z online spending behavior and investigates the moderating role of advertising relevance within Indonesia’s emerging digital market. Design/methodology/approach-This study employed a quantitative explanatory approach using a cross-sectional survey design. Data were collected from 420 Generation Z consumers aged 18–27 years who actively participated in online shopping activities. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The conceptual framework was primarily grounded in the Stimulus–Organism–Response (SOR) framework and supported by complementary insights from the Technology Acceptance Model (TAM). Finding/Results - The findings indicate that digital advertising effectiveness positively and significantly influences online spending behavior and emerged as the strongest predictor in the model (β = 0.364, p < 0.001). Advertising relevance also demonstrated a significant direct effect (β = 0.154, p < 0.001) and strengthened the relationship between digital advertising effectiveness and online spending behavior (β = 0.114, p = 0.003). Digital literacy additionally contributed positively to online spending behavior (β = 0.171, p < 0.001). The structural model explained 27.8% of the variance in online spending behavior (R² = 0.278), indicating modest but meaningful explanatory capability. Originality/Value - This study contributes to digital advertising and consumer behavior literature by demonstrating that advertising relevance functions both as a direct behavioral driver and as a contextual enhancer of digital advertising effectiveness in shaping Generation Z online spending behavior within an emerging market context. The findings also highlight the importance of personalization, contextual suitability, and consumer-oriented advertising strategies for improving digital engagement and purchasing outcomes.